PENGARUH FAKTOR KEPERILAKUAN TERHADAP KEGUNAAN SISTEM KEUANGAN AKUNTANSI DAERAH DI KOTA MALANG - Shella Citra Oktaviani; Abdul Wahid Mahsuni; Afifudin Afifudin (Universitas Islam Malang, 2020)
This study aims to determine the effect of behavioral factors on the use of the Regional Accounting Financial System in Malang. The variables used in this study are Attitudes, Emotions and Motivation towards the Regional Financial Accounting System. The sample in this study was 53 BPKAD Malang City employees. From the test results using multiple linear regression models obtained results simultaneously Variable Attitudes, Emotions and motivation affect the financial system of Regional Accounting. Partial test results show attitudes and motivation affect the Regional Accounting financial system, Partial test results indicate Emotion has no effect on the Regional Accounting financial systemKeywords: Regional Financial Accounting System, Attitude, Motivation, Emotion